Ultrasound-assisted one-phase solvent extraction coupled with liquid chromatography-quadrupole time-of-flight mass spectrometry for efficient profiling of egg yolk lipids. (30th July 2020) - Xie, Ya; Wu, Bangfu; Wu, Zongyuan; Tu, Xinghao; Xu, Shuling; Lv, Xin; Yin, Hongqing; Xiang, Jiqian; Chen, Hong; Wei, Fang
Highlights: A new ultrasound-assisted one-phase solvent extraction method for comprehensive lipids extraction is proposed. Significant improvement of the lipids extraction efficiency was obtained using the optimized IPA-USAE method. Untargeted exhaustive lipid profiling of egg yolks was achieved by IPA-USAE combined with UPLC-Q-TOF-MS. The proposed method is potentially applicable to comprehensive profiling of lipids in other biological samples. Abstract: In this research, a novel ultrasound-assisted extraction (USAE) method using a one-phase solvent (isopropanol, IPA) combined with liquid chromatography-electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QToF-MS) was developed for exhaustive profiling of egg yolk lipids, which are considered to be essential nutrients that have important functions for human health. Compared with IPA-vortex extraction method, the optimized IPA-USAE method shows better performance in terms of extraction time, lipid losses, lipid recoveries and the number of lipids identified. With this established simple, high throughput and reliable analytical approach, untargeted comprehensive lipid profiling of four kinds of egg yolks was achieved, thus providing a powerful tool for nutritional research of egg lipids. Considering that the lipids contained in egg yolk are quite abundant in both quantity and species, the proposed IPA-USAE combined with LC-ESI-QToF-MS is also potentially applicable to comprehensive extraction and profiling of lipids in other biological samples.